2016
DOI: 10.5604/20831862.1185889
|View full text |Cite
|
Sign up to set email alerts
|

Poor physical fitness is independently associated with mild cognitive impairment in elderly Koreans

Abstract: The purpose of this study was to investigate the association between physical fitness and mild cognitive impairment (MCI) in elderly Koreans. This was a cross-sectional study that involved 134 men and 299 women aged 65 to 88 years. Six senior fitness tests were used as independent variables: 30 s chair stand for lower body strength, arm curl for upper body strength, chair-sit-and-reach for lower body flexibility, back scratch for upper body flexibility, 8-ft up-and-go for agility/dynamic balance, and 2-min wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…Consistent with our finding, previous studies have demonstrated that lower functional mobility is associated with lower global cognitive function, as well as executive function and processing speed . These studies included not only community‐dwelling older adults but also older people who were institutionalized, consisting of those with a variety of cognitive level from normal to pathological conditions such as MCI and dementia.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our finding, previous studies have demonstrated that lower functional mobility is associated with lower global cognitive function, as well as executive function and processing speed . These studies included not only community‐dwelling older adults but also older people who were institutionalized, consisting of those with a variety of cognitive level from normal to pathological conditions such as MCI and dementia.…”
Section: Discussionsupporting
confidence: 90%
“…Poor flexibility may not represent limited joint motion, but it rather affects the physical functioning and independence. Study conducted by Lee et al (2016) to evaluate the relationship between SFT and cognitive function also reported that upper body flexibility as assessed using back scratch test and agility as assessed using 8 foot up-and-go were better among older adults without MCI compared to those with MCI. Fujiwara et al (2013) also revealed that higher grip strength was observed among subjects with normal cognition as compared to subjects with MCI.…”
Section: Discussionmentioning
confidence: 95%
“…A few studies that have been discussed above involved the determination of MCI based on MMSE (Jang & Kim 2015;Lee et al 2016) and MoCa (Fujiwara et al 2013) assessments only. However, none of the above-mentioned studies defined the MCI based on Peterson criteria (2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These situations in Tables 9 and 10 are an indication that in addition to making the movements more stable, the use of the system makes training more accurate, so physical and cognitive abilities related to the movements are increased as stated in [93][94][95].…”
Section: The Effect Of the System On Physical And Cognitive Developmentmentioning
confidence: 98%